Effectuation theoretical debate: Systematic review and research agenda - Suzi Elen Ferreira Dias; Edson Sadao Iizuka; Eduardo Pinto Vilas Boas (Innovation & Management Review, 2020)
Purpose - The purpose of this paper is to understand the theoretical discussion of effectuation since the seminal paper in 2001 and to propose an agenda for future studies. Design/methodology/approach Systematic literature review and content analysis of 71 papers. Findings Most papers performed a replication of the concepts empirically, and few studies proposed to understand theoretical aspects of effectuation, among them, some authors presented theoretical advances to improve the approach and others participated in an ongoing debate that shows there is no consensus on whether the approach is theory or if considered, appears to be under construction at a rudimentary level or being questioned. Research limitations/implications The method requires authors to make choices, so the database used and the criteria defined for searching papers that were analyzed are the main limitations of this research. Practical implications The authors suggest that researchers, teachers and practitioners use effectuation analytically and reflectively. Social implications The authors present and analyze the current theoretical debate on effectuation. Results suggest the need for new discussions about the concepts, as well as new theoretical efforts of the researchers to analyze the potentialities and limitations of this approach. Originality/value Among empirical and applied research, with replications of the concepts of effectuation, this research contributes to a theoretical discussion based on a systematic literature review, seeking to bring new reflections about this approach. Additionally, the authors present an agenda of theoretical gaps for the development of future research.
Keywords: 650; Literature review; Academic production; Effectuation limitations; Research agenda